Prevalence and Correlates of Mental Health of University Students in Hong Kong: What Happened One Year After the Occurrence of COVID-19? - Shek, Daniel T. L.; Dou, Diya; Zhu, Xiaoqin (Frontiers in Public Health, 2022)
Purpose: In this study, we studied the prevalence and correlates of mental health problems (depression, anxiety, and stress) in Hong Kong university students after one year of the occurrence of COVID-19. We examined the relationships between mental health problems and socio-demographic factors (including living status and economic strain), need satisfaction, and difficulties encountered. Methods: A cross-sectional online survey involving 1,648 university students (Mean age = 20.09 years ± 1.37) was conducted. They responded to a questionnaire assessing their mental health (including the Depression, Anxiety, and Stress Scales - DASS), psychosocial resources, social support, need satisfaction, difficulties and challenges, and evaluation of services they had received. Results: Based on DASS-21 cutoff scores, prevalence rates of moderate or above for depression, anxiety and stress were 40.0%, 50.7%, and 22.2%, respectively. While age and gender were not related to the DASS measures, economic strain and living alone were positively related to negative emotional states. Multiple regression and PROCESS analyses showed that need satisfaction and difficulties contributed to depression and anxiety, with stress as a mediating factor. Conclusions: The proportions of students who experienced moderate and above levels of depression (40.0%), anxiety (50.7%), and stress (22.2%) indexed by DASS deserve attention. Living alone and experienced economic disadvantage are risk factors for negative emotional states. Need satisfaction and life challenges are related to negative emotional states. Need satisfaction and difficulties contributed to stress experienced which further influence anxiety and depression.